(untitled) (Nigerian Journal of Technology, 2018)
The pyrolysis of waste low-density polyethylene (LDPE) is an excellent method of converting waste materials into useful products. Aspen HYSYS 2006 was used to develop a computational steady-state model to simulate the pyrolysis of LDPE. The Peng-Robinson fluid package was used for the simulation. A continuous stirred tank reactor with an Arrhenius kinetic expression was used to predict reaction extent and product yield. At a pyrolysis temperature of 4500C and atmospheric pressure, 92.88% liquid yield was obtained. From the given feedstock, the char obtained was composed of only elemental carbon. The synthesis gas was composed mainly Hydrogen and C1-C4 hydrocarbons with traces of n-C5 and n-C6. The Pyrolysis oil was composed of higher hydrocarbon fractions (C8-C24). The conversion-temperature relationships from the simulation are in good agreement with experimental results. This proved that pyrolysis of waste LDPE can give an excellent yield of liquid product and is a viable recycling technique. http://dx.doi.org/10.4314/njt.v37i4.12